Drug-specific laterality effects on frontal lobe activation of atomoxetine and methylphenidate in attention deficit hyperactivity disorder boys during working memory. Issue 3 (19th April 2013) - Cubillo, A.; Smith, A. B.; Barrett, N.; Giampietro, V.; Brammer, M.; Simmons, A.; Rubia, K.
Abstract : Background: The catecholamine reuptake inhibitors methylphenidate (MPH) and atomoxetine (ATX) are the most common treatments for attention deficit hyperactivity disorder (ADHD). This study compares the neurofunctional modulation and normalization effects of acute doses of MPH and ATX within medication-naive ADHD boys during working memory (WM). Method: A total of 20 medication-naive ADHD boys underwent functional magnetic resonance imaging during a parametric WM n-back task three times, under a single clinical dose of either MPH, ATX or placebo in a randomized, double-blind, placebo-controlled, cross-over design. To test for normalization effects, brain activations in ADHD under each drug condition were compared with that of 20 age-matched healthy control boys. Results: Relative to healthy boys, ADHD boys under placebo showed impaired performance only under high WM load together with significant underactivation in the bilateral dorsolateral prefrontal cortex (DLPFC). Both drugs normalized the performance deficits relative to controls. ATX significantly enhanced right DLPFC activation relative to MPH within patients, and significantly normalized its underactivation relative to controls. MPH, by contrast, both relative to placebo and ATX, as well as relative to controls, upregulated the left inferior frontal cortex (IFC), but only during 2-back. Both drugs enhanced fronto-temporo-striatal activation in ADHD relative to control boys and deactivated the default-mode network, which were negatively associated with the reduced DLPFC activation and performance deficits, suggesting compensation effects. Conclusions: The study shows both shared and drug-specific effects. ATX upregulated and normalized right DLPFC underactivation, while MPH upregulated left IFC activation, suggesting drug-specific laterality effects on prefrontal regions mediating WM.